Spatiotemporal Diffusion Patterns Associated with COVID-19 in the Tel Aviv-Jaffa and Haifa (Israel) Metropolitan Regions - Adi Ofir; Motti Zohar (Geographies)
Social and cultural diffusion determines how behavioral phenomena spread among communities. The COVID-19 pandemic, which emerged globally at the beginning of 2020, triggered changes in human behavior in various settlements and regions. In this study, we use a spatial approach to examine diffusion patterns during the Omicron wave (December 2021–February 2022). We collected data on daily testing and confirmed cases from the Israeli Ministry of Health (MoH) database, as well as population characteristics from the Israel Central Bureau of Statistics (CBS). These data were normalized per population, classified regionally and analyzed spatially using GIS, to verify the significance of the results. We found a contagious diffusion pattern apparent spatially in the metropolitan regions of Tel Aviv-Jaffa and Haifa (Israel). Accordingly, the undulating pattern of the number of COVID-19 tests and confirmed cases began in the center of the given metropolitan region (populated with high-class settlements) at the beginning of the wave, spread out to the periphery (populated with high-class settlements) toward the mid-wave period, and returned to the center when the wave ended. Additionally, we have seen that these patterns do not accord with the morbidity spread, implying that social characteristics may have been dominant in determining the diffusion pattern.